The Influence of Social Media Marketing Activities Towards Purchase Intention Mediated by Customer Relationships in the Case of Tokopedia Indonesia - Jason Wijaya; Alvianto Wiratama (iBuss Management, 2023)
The rapid expansion of social media users in particular has revealed significant shifts in how society interacts. Brands must now pay attention to customer involvement on social media to result in a direct or indirect purchase intention in order to boost sales and revenue. In addition to social media marketing activities (informativeness, interactivity, trendiness, personalization, and word of mouth), the study model analyzes the role of customer relationships as a mediating variable. This study focuses on Tokopedia users in Indonesia who have seen Tokopedia’s marketing contents on Instagram. Using a simple random sampling procedure, a questionnaire was spread throughout social media platforms. Then, the PLS-SEM method was used to evaluate 119 valid respondents. Analysis revealed a positive impact between social media marketing activities on purchase intention, as well as a positive impact on the relationship between customer relationships and purchase intention. Results also indicated that the relationship between social media marketing activities and purchase intention is partially mediated by customer relationships.Keywords: social media marketing activities, customer relationships, purchase intention, Tokopedia Indonesia.